Pengaruh Live Stream, Time Pressure dan Streamer Credibility terhadap Impulse Buying Penonton Live Stream pada Platform TikTok Shop di Surabaya - Ramadhan, Marsay Zikra; Amelia, Ratih (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
The growth of live stream commerce in Indonesia, particularly on the TikTok Shop platform, has transformed consumer decision-making patterns from planned processes into spontaneous responses to real-time stimuli. This study aims to analyze the influence of live stream, time pressure, and streamer credibility on impulse buying behavior among TikTok Shop live stream viewers in the beauty and skincare category in Surabaya. The approach used in this study is causal quantitative with data analysis using the partial least squares structural equation modeling (PLS-SEM) method assisted by SmartPLS 3.0 software. A total of 200 respondents were determined as the sample through purposive sampling technique with the main criterion of having made an unplanned purchase during a TikTok Shop live stream session. Data were collected through a five-point Likert scale questionnaire consisting of 36 statements. The test results indicate that live stream and time pressure each have a positive and significant effect on impulse buying, whereas streamer credibility was not proven to have a significant effect despite the positive direction of the relationship. These findings imply that optimizing broadcast quality and time pressure strategies are the primary priorities for business actors in driving sales conversion on live stream e-commerce platforms.